Strategi Pendidikan Life Skills di Masa Covid 19 Pondok Pesantren Mamba’ul Ma'arif Denanyar Jombang - Waslah, Waslah; Sari, Herliany Nela (Universitas KH. A. Wahab Hasbullah, 2022)
After the outbreak of covid 19, a lot of education is less effective in learning. The education system began to look for new innovations for teaching and learning activities. So that learning can be maximized later. Interaction restrictions are an obstacle for someone to carry out learning activities. Life skills education at Mamba’ul Ma’arif boarding school, Denanyar Jombang, is carried out to develop students self in the skills they have, so they can face life’s problems. The formulation of the problem in this study is, how is the strategy for life skills education during the covid 19 period, as well as the supporting and inhibitting factors at the Mamba’ul Ma’arif Islamic Boarding School Denanyar Jombang. The approach used in this research is a qualitative approach with the type of case study research. The method used is observation, interviews, and documentation. The results of this study indicate that the strategy of the Islamic boarding school. Mentor, ustadz, ustadzah and students have interacted and formed well. And the implications made have been able to equip students to apply their life skills in society. Various suggestions that can be taken into consideration in providing life skills at Mamba’ul Ma’arif Islamic Boarding Shool Denanyar Jombang.